Soft tissue perineurioma involving the kidney: a report of two cases with an emphasis on differential diagnosis - Tian-shi Ma; Ling Zhou; Quan Zhou; Xiang-lei He; Ming Zhao (BMC, 2021)
Abstract Background Soft tissue perineurioma of the kidney is rare, with only a few reported cases. We report two additional cases with histologic, immunohistochemical and genetic analyses. Case presentation Both tumors were from adults (1 female aged 49 years and 1 male aged 42 years) and grossly had maximum diameters of 6.5 and 10 cm, respectively. The tumors were overall well circumscribed but unencapsulated, with focally entrapped benign native renal tubules in one case; both tumors seemed to arise in the capsular areas. The tumors had histologic and immunohistochemical profiles consistent with soft tissue perineurioma. Fluorescence in situ hybridization analyses demonstrated that the tumors were negative for amplification of MDM2 and rearrangements of ESWR1, FUS, and KMT2A. Targeted next-generation sequencing revealed a low tumor mutation burden and likely pathogenic mutations (CYP2B6 and FLT1 mutations for 1 each). Follow-up data were available for both patients; neither had tumor recurrence or metastasis. Conclusions In conclusion, renal perineurioma is rare, usually arises in the capsular areas, and is cured by resection. Low-grade dedifferentiated liposarcoma and low-grade fibromyxoid sarcoma as well as other spindle cell lesions should be considered in the differential diagnosis.